Incorporating Digital Environment into the Subject Area of Higher Educational Institution - Natalia A. SHUMAKOVA; Marina V. SAVELYEVA (Communications of International Proceedings, 2021)
The times of pandemic makes in-class education become entirely on-line; although, the conventional university education has always searched for new forms to provide the students with possible choices, but the lack of alternatives in tuition has perplexed the university society: both administration, educators, students and their parents. The fast transition to a digital environment reveals its incompleteness, unavailability to meet the requirements of the education process. Moreover, during that experience the educators could not pay any special attention to the heterogeneity of students and educators as one of the critical factors in selecting a successful training environment. The research focuses on the characteristics of different education modes; it analyses the challenges of distant education and demonstrates that transition backward to the in-class education presents its unexpected formidable assignments.
Keywords: Millenials; Digitalization; Training-Learning Environment.